Evaluación de macro y micro invertebrados como indicadores biológicos de la calidad de agua del húmedal Amidas del parque Nacional Llanganates en la provincia de Cotopaxí. - Porras Bonilla, Kevin Israel (2017)
For the development of the present investigation the main objective was: To evaluate the quality of water through macro and micro invertebrates in the wetland amides of the canton Salcedo of the province of Cotopaxi. We used the methodologies based on BMWP "Biological Monitoring Working Party", which allows to evaluate the quality index Ephemeroptera, Plecoptera, Trichoptera (E.P.T), and for the Biodiversity Index we used parameters established by Shannon Weaver. A physical, chemical and microbiological analysis was then performed to validate the biological information obtained. The INEN 2 169: 98 Ecuadorian Technical Standard was used for the collection of bioindicators. A total of 1,057 aquatic invertebrate individuals were identified, grouped in 10 families, belonging to (Hyalellidae, Notonectidae, Sphaeriidae, Planariidae) being the most representative, as far as the E.P.T index was not applied since no species of these families were found. In the study of the micro invertebrates were found 6 families of diatoms, the lowest tolerance to the contamination of the species Frustulia vulgaris, followed by the diversity index of Shannon obtaining a score of 5.32. The BMWP index revealed that the Amides wetland shows type III contamination (moderately contaminated water), the physical, chemical and microbiological parameters do not exceed the permissible limits established in the environmental norm on the admissible Quality Criteria for the preservation of flora and fauna in fresh, cold or warm waters, marine and estuarine waters for the quality of water and environment of Book VI, Annex I, TULSMA. Key words: Micro invertebrates, BMWP, E.P.T, Shannon Index, Wetland.